Comprehensive analysis of the diagnostic and therapeutic value, immune infiltration, and drug treatment mechanisms of GTSE1 in lung adenocarcinoma - Yan, Guanqiang; Li, Jingxiao; Gao, Xiang; Liu, Jun; Feng, Guiyu; Li, Yue; Zhou, Huafu (Frontiers in Medicine, 2024)
Objective: The aim of this investigation was to assess the diagnostic and therapeutic efficacy of G2 and S-phase expressed 1 (GTSE1) in lung adenocarcinoma (LUAD), while examining its impact on immune infiltration and drug treatment mechanisms.Methods: This research involved examining the expression patterns and diagnostic accuracy of GTSE1 in LUAD using various databases and clinical samples. The databases utilized included Gene Expression Omnibus (GEO), Clinical Proteomic Tumor Analysis Consortium (CPTAC), and The Cancer Genome Atlas (TCGA). Both gene expression and protein levels were analyzed. Subsequently, the prognostic ability of GTSE1 was evaluated based on clinical follow-up data using methods such asusing univariate, multivariate, and prognostic meta-analysis. Additionally, potential mechanisms of action of GTSE1 were explored through enrichment analysis.Furthermore, the correlation between GTSE1 expression and the tumor microenvironment, immune cell infiltration, and immune checkpoints was assessed using ESTIMATE and CIBERSORT algorithms. The effectiveness of chemotherapy and targeted therapy was predicted using the 'pRophetic' R package, which analyzed gene expression data.Results: Analysis of GEO data, CPTAC data, TCGA data, and clinical samples revealed increased levels of GTSE1 in LUAD tissues. Enhanced GTSE1 expression demonstrated excellent diagnostic accuracy and served as a significant prognostic indicator for LUAD patients. GTSE1 expression emerged as an independent predictive factor in both univariate and multivariate Cox regression analyses. Furthermore, functional enrichment analysis suggested a potential association between GTSE1 and the cell cycle, p53 signaling pathway, as well as ubiquitin-mediated protein degradation.High expression of GTSE1 was associated with increased immune cell infiltration and heightened sensitivity to a specific type of chemotherapy and targeted drugs.Conclusions: Increased expression of GTSE1 in patients with LUAD showed significant diagnostic and prognostic significance. It was also associated with increased immune infiltration and an unfavorable response to targeted medication.